KONTRIBUSI MAHASISWA KAMPUS MENGAJAR DALAM MENINGKATKAN LITERASI NUMERASI SD NEGERI 24 KOTA SORONG: CONTRIBUTION OF TEACHING CAMPUS STUDENTS IN IMPROVING THE LITERACY AND NUMERACY ABILITIES OF STATE ELEMENTARY SCHOOL 24 SORONG CITY - Pratiwi, Putri Dini Retno; Trisnawati, Nika Fetria; Kumalasari, Lina; Agnes Tondatuon, Helena (KAMBIK: Journal of Mathematics Education, 2024)
Instruction plays a critical part in moving forward the quality of Human Assets (HR), and is the most important in shaping a quality future era. Successful instruction not only gives rise to knowledge but also makes a difference in the advancement of demeanors, values, and abilities. Be that as it may, instruction still faces major challenges in Indonesia, such as moo proficiency and numeracy among understudies. This inquiry points to making strides in the proficiency and numeracy aptitudes of lesson V understudies at SD Negeri 24 Sorong City through the Instructing Campus program executed from 26 February to 16 June 2024. A subjective and graphic approach was utilized in this inquiry about perception, meeting, and documentation strategies. The investigation shows that this program is compelling in expanding understudy engagement through different intuitive exercises such as Computerized Proficiency, Wordsearch Amusement, Tallying Whereas Lining Up, and Numeracy Snakes and Steps. Understudies appear to have increased motivation and learning capacity, as well as a distant better; a much better; a higher; a stronger; an improved">a distant better understanding of education and numeracy concepts. In conclusion, the Educating Campus program has had a positive effect in making a wonderful and conducive learning environment and making strides in the quality of instruction at SD Negeri 24 Sorong City.